Awareness of Parents Regarding Eye Diseases and Eye Care Needs among Children of Tehsil Babuzai, District Swat: Doi: 10.36351/pjo.v39i3.1509 - Khan, Suzzana Akbar; Nabeel , Khizar; Muhammad, Idrees; Batool, Siddiqa; Javed, Sadaf (Pakistan Journal of Ophthalmology, 2023)
Purpose: To find out level of awareness of parents regarding eye diseases, eye care needs and eye care practices among children of district Swat. Study Design: Descriptive Cross-sectional study. Place and Duration of Study: Hospitals of Tehsil Babuzai, District Swat, Pakistan from 15th March to 15th August 2022. Methods: This cross-sectional study was carried out on 200 parents of Tehsil Babuzai, District Swat, Pakistan. Data was collected through an interview-based questionnaire which was divided into four main parts; socio-demographic data, knowledge about eye care, knowledge about eye diseases and eye care practices. Chi-square test was used to find out association among categorical variables. Data was analyzed using SPSS version 26. Results: Knowledge about eye care was good in 112 parents (56.0%) and poor in 88 parents (44.0%). Knowledge was good regarding amblyopia in 82 (41.0%) parents, for childhood cataract in 63 (31.5%), and for congenital glaucoma in 56 (28.0%) parents. Attitude regarding children wearing spectacles and allowing ophthalmic surgery was positive in 179 (89.5%) and 165 (82.5%) parents, respectively. Most common eye diseases identified were refractive error (50.9%), followed by amblyopia (23.6%). Participants with higher education level and those having child with existing eye problems had significantly higher knowledge and practices scores (p < 0.05). Conclusion: A considerable heterogeneity was observed between different social groups regarding children’s ocular problems and practices. Health care communities must play their role in communicating health information to illiterate parents in order to improve their knowledge and practices regarding ocular issues of their children.